Sensor Systems and Networks: Phenomena, Technology, and Applications for NDE and Health Monitoring 2007 2007
DOI: 10.1117/12.715994
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and evaluation of cracked beams based on nonlinear wave modulation

Abstract: In this paper, the applicability of a nonlinear wave modulation-based crack monitoring methodology has been experimentally investigated. Experiments using a beam specimen with a low-cycle fatigue crack have been conducted for the purpose of preliminary study, in which two PZT patches attached on the beam have been used as the transducer of high frequency probe wave. When the specimen is subjected to a harmonic loading at low frequencies, it vibrates, and the presence of the crack introduces a nonlinear effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Experimental evidences have shown that this modulation is very sensitive to unexpected presence of imperfect bonding of solids, such as cracks, debonding, preload-loss in bolted joints, etc.. 2,11 Hence, the quantification of NWM, which is usually done by measuring the magnitude of the sidebands in the frequency domain, could be a sensitive measure of incipient contact-type defects. Masuda et al have presented a NWM-based structural health monitoring methodology which enables the integrity monitoring of a bolted joint 8 as well as the crack growth monitoring 10 for a beam structure. Differently from most of the previous works, the received probe waveforms have been demodulated in the time domain and examined as a potential indicator of the damage extent.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidences have shown that this modulation is very sensitive to unexpected presence of imperfect bonding of solids, such as cracks, debonding, preload-loss in bolted joints, etc.. 2,11 Hence, the quantification of NWM, which is usually done by measuring the magnitude of the sidebands in the frequency domain, could be a sensitive measure of incipient contact-type defects. Masuda et al have presented a NWM-based structural health monitoring methodology which enables the integrity monitoring of a bolted joint 8 as well as the crack growth monitoring 10 for a beam structure. Differently from most of the previous works, the received probe waveforms have been demodulated in the time domain and examined as a potential indicator of the damage extent.…”
Section: Introductionmentioning
confidence: 99%
“…Since a solid without contact-type failures hardly shows NWM, and it can be believed that the more severe damage induces more intense NWM the intensity of the NWM can be a baseline-free measure of contact-type failures. Because both the transmitter and receiver for the probe actuation and sensing can be easily replaced by structural embeddable smart materials such as piezoelectric active sensors, NWM-based approaches have been pursued as another promising SHM method [40][41][42] for incipient damage evaluation.…”
Section: Introductionmentioning
confidence: 99%